Chromitite deposits of Ufaley ultramafic massif (South Urals) - D. E. Saveliev (Georesursy, 2024)
Data on the morphology, composition, textural and structural features of chromite deposits of the Ufaley ultramafic massif are presented. The mineralogical and compositional features of the host ultramafic rocks allow us to interpret them as depleted restite from partial melting of mantle peridotites. Relatively wide variations in the composition of ore-forming chromian spinel grains (#Cr 0.6–0.8) and noticeable metamorphism of disseminated ores with replacement of chromite by Cr-magnetite are noted. It is assumed that chromitite bodies were initially formed under the conditions of the upper mantle by a rheomorphic mechanism, and then their structural and geochemical transformation took place in the collisional setting of the upper part of the crust. Flattened bodies of disseminated chromitites have been preserved near competent gabbroid blocks, while other deposits have been transformed into lenses and podiform bodies of densely disseminated and massive ores of smaller size. The “cold tectonics” of the crustal stage led to the disintegration of deposits and the simultaneous local enrichment of deformed chromitite bodies.